2021
DOI: 10.1016/j.ssmph.2021.100808
|View full text |Cite
|
Sign up to set email alerts
|

Operationalization of intersectionality in physical activity and sport research: A systematic scoping review

Abstract: Participation in and opportunities for physical activity (PA) and sports (PA inclusively hereafter) are known to vary across individuals with different social positions. Intersectionality theory may help us to better understand the complex processes of multiple interlocking systems of oppression and privilege shaped by intersections of individuals’ social categories. The objectives of this systematic scoping review were (1) to summarize the findings of articles examining PA claimed operationalization of inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 76 publications
0
23
0
1
Order By: Relevance
“…In addition to 2018 India's Report Card, 16 a few recent studies have found that intersectionality is a useful framework in investigating disparities and inequalities beyond sex/gender in behavior research. 46 , 47 , 48 …”
Section: Gaps and Future Recommendationsmentioning
confidence: 99%
“…In addition to 2018 India's Report Card, 16 a few recent studies have found that intersectionality is a useful framework in investigating disparities and inequalities beyond sex/gender in behavior research. 46 , 47 , 48 …”
Section: Gaps and Future Recommendationsmentioning
confidence: 99%
“…• A dearth of research on women and girls who face multiple systems of oppression in accessing, participating in, or leading sport (Lim et al, 2021); • Consistent application of a "women-first" model of equity wherein White, nondisabled, heterosexual, cis-women are prioritized as equity-deserving in sport "before" equity for "other" identity groups (e.g., people who are racialized, Indigenous, two-spirit, trans and/or nonbinary, disabled) can be considered; and • A misuse of "gender" which tends to exclude nonbinary and transgenders and assumes homogeneity of nonbinary and transexperiences.…”
Section: Commitments To Action: Context Of the Operationalizing Inter...mentioning
confidence: 99%
“…According to Lim et al (2021), intersectionality has mainly been mobilized in sport research to qualitatively investigate varying axes of marginalization beyond sex/gender, with a special focus on race and ethnicity in the context of sport participation. This literature corpus examined how varying intersections of social categories impacted individuals' opportunities to participate in sport.…”
Section: The Importance Of Intersectional Approaches and Action In Sp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on physical activity discuss equity and equality, in the context of the EDI groups of gender [42], race [122][123][124][125], and LGBTQ2S+ [126], including through an intersectionality lens [127][128][129][130] of these three identities [53]. The same is true for the terms diversity and inclusion [126], as well as for Indigenous peoples [62].…”
Section: The Individual Concepts Of Equity Equality Diversity and Inc...mentioning
confidence: 99%